Correction: Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes. Issue 20 (23rd February 2023) - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al.
Abstract : Correction for 'Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii ) complexes' by Philipp Dierks et al., Chem. Commun., 2021, 57, 6640–6643, ; https://doi.org/10.1039/D1CC01716K .